Type II Congenital Pulmonary Airway Malformation in an Esophageal Lung. Issue 3 (2013) - Martínez-Martínez, Blanca Estela; Furuya, María Elena Yuriko; Martínez-Muñiz, Irma; Vargas, Mario H; Flores-Salgado, Rosalinda
Abstract : A seven-month-old girl, born prematurely (birth weight 1000 g) from a twin pregnancy, was admitted to hospital due to recurrent pneumonia and atelectasis. She experienced cough and respiratory distress during feeding. The right hemithorax was smaller than the left, with diminished breath sounds and dullness. Chest x-rays revealed decreased lung volume and multiple radiolucent images in the right lung, as well as overdistention of the left lung. An esophagogram revealed three bronchial branches arising from the lower one-third of the esophagus, corresponding to the right lung and ending in a cul-de-sac. A diagnosis of esophageal lung was established. On bronchography, the right lung was absent and the trachea only continued into the left main bronchus. Echocardiography and angiotomography revealed agenesis of the pulmonary artery right branch. The surgical finding was an esophageal right lung, which was removed; the histopathological diagnosis was type II congenital pulmonary airway malformation in an esophageal lung.